Multi-parameters measurement based on cascaded Bragg gratings in magnetic fluid-infiltrated photonic crystal fibre. Issue 8 (28th April 2017) - Liu, Hai; Tan, Ce; Zhu, Chenghao; Wang, Yan; Ma, Hanlin
Abstract: Simultaneous measurement of multi-parameters is demonstrated quantitatively using two fibre Bragg gratings inscribed on a high birefringence photonic crystal fibre (PCF) and common PCF, respectively. The birefringence coefficient and the Bragg wavelengths corresponding to the fast-axis mode and slow-axis can be magnetic-controlled by filling magnetic fluid (MF) into several cladding air-holes. Based on the dependence of the MF refractive index on temperature and magnetic field, the sensitivity of the spectral response of the device to longitudinal strain, magnetic field and temperature are characterized, and the results of its application as a multi-parameter sensor are also presented.